Extension in Collective Health, Communication and Culture: experiencing interdisciplinarity in Communication and Health - Lóss Fernandes da Silva, Patrick; Sinesio Ohnesorge, Sara; Brum Ferreira, Ágata; Sofia Bruzzi Barcelos Lima, Bárbara; Gonçalves Souza, Maria Luiza; Mascarelo da Silva, Thalita; dos Santos Neto, Edson Theodoro; Emmerich Oliveira, Adauto; Pinheiro Bernadi Primo, Paola (Guará Journal, 2025)
The Extension Program Collective Health, Communication, and Culture is conceived as a space of student protagonism in the field of Communication and Health, fostering relevant contributions through diverse academic practices. Between August 2022 and August 2023, activities were mapped based on documentary and bibliographic research, encompassing three projects: the Health in the Media Observatory – Espírito Santo (OSM-ES), the Laboratory of Projects in Collective Health (LAPROSC), and VideoSaúde Coletiva (VSC). During this period, five scholarship students from the Journalism and Occupational Therapy programs were directly involved in the execution of actions, which resulted in three undergraduate research projects, eight press releases, forty-five Instagram posts, one event recording, and fourteen institutional texts. These experiences fostered interdisciplinary exchanges among students from different fields of knowledge and contributed to their training in research and extension, promoting fruitful dialogue with diverse audiences through LAPROSC meetings, VSC activities, and scientific, media, and journalistic productions within OSM-ES.
Keywords: Extension Program; Scientific dissemination; Communication and Health